Spray pyrolysis deposition of undoped SnO2 and In2O3 films and their structural properties. Issue 1 (February 2017) - Korotcenkov, G.; Cho, B.K.
Abstract: In this paper the results of structural analysis of the SnO2 and In2 O3 films deposited by spray pyrolysis are presented. The main goals of this analysis are summarizing the results obtained in this field, highlighting a correlation between parameters of film deposition and the material structure and formulating some general regularities, typical for metal oxides. Peculiarities and mechanisms of pyrosol deposition as well as advantages and disadvantages of this technology for deposition of the films with required parameters were also discussed. It is shown that this technology has great potential for controlling structural parameters of metal oxides such as thickness, the grain size, texturing, roughness, the grain faceting and the porosity.